Evaluasi Kinerja Portal New Student UIGM Berdasarkan Perspektif Mahasiswa Menggunakan Metode Use Questionnaire dan Importance Performance Analysis (IPA) - Juliansyah, Muhammad Agung; Terttiaavini; Heryati, Agustina; Sanmorino, Ahmad (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
This study evaluates the performance of the New Student Portal at Universitas Indo Global Mandiri (UIGM) Palembang from the students’ perspective. The respondents include 295 active students from the Faculty of Computer Science who have used the portal for at least one semester. A quantitative approach was used with Probability Sampling. Data were analyzed using path analysis with SmartPLS 4.0, based on the USE Questionnaire, which includes indicators of Usefulness, Ease of Learning, Ease of Use, and Satisfaction. Results show that usability scored 84.25%, information quality 84.45%, and service quality 81.33%, all of which significantly and positively influence user satisfaction. The study also offers recommendations to improve the portal’s quality and serve as a reference for future research.